TAKAFUL INDUSTRY IN MALAYSIA: OVERVIEW OF KEY STRATEGIES AND REGULATORY FRAMEWORK - NorAin Binti Mohammad Sopian; Dr Adi Anuar Bin Azmin (Journal of Islamic, Social, Economics and Development, 2021)
This paper outlines the history of Takaful industry in Malaysia and how this industry evolves through time. The growth of Islamic financial system has directed Takaful industry to experience a rapid progress and expansion as this industry enhance the application of Shariaah compliant laws in terms of protecting the consumer towards risk and vulnerability arising from untoward events. The reasons why Malaysia has become the central movement in Takaful within ASEAN region and second biggest market in the world is due to the support given by the Malaysian government where there are efforts in creating beneficial environment, regulation enhancement and strengthening. Thus, this paper discussed on the key strategies and regulatory framework imposed within Takaful industries and suggest recommendations to multiply the expansion and increase market awareness towards Takaful industry.